Long-Run Saving Dynamics: Evidence from Unexpected Inheritances - Jeppe Druedahl; Alessandro Martinello (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2017)
We exploit inheritance episodes to provide novel causal evidence on long-run saving dynamics. For identification, we combine a panel of administrative wealth reports with the unexpected timing of sudden parental deaths. After inheritance, net worth converges towards the path established before parental death, and convergence is faster for liquid assets. Using a generalized structural framework, we show that buffer-stock and two-asset models can fit these dynamics, but only if agents are impatient enough and have both strong precautionary and post-retirement saving motives. Relative to standard calibrations, such agents have at least 50 percent higher precautionary savings for given total wealth.
Keywords: D14; D91; E21; G11; G40; 330; Inheritance; saving dynamics; consumption; buffer-stock; structural; causal; convergence; precautionary